Protective effect of tetramethylpyrazine against damages of aortic endothelial cells elicited by low-density lipoproteins - Li Yu-jie; Li Yuan-jian; Wu Jin-xiang; Yu Xian-jie; Yan You-fang (Acta Pharmacologica Sinica, 2016)
Effects of tetramethylpyrazine (TMP) on endothelial cells damaged by low-density lipoproteins (LDL) were investigated. When endothelial cells were incubated with LDL (1.5 mg protein.ml-1) the level of malondialdehyde (MDA) was increased and the activity of superoxide dismutase (SOD) was inhibited, and levels of cGMP and epoprostenol were decreased. TMP at concentrations of both 20 and 150 mg.L-1 nullified the inhibition of SOD activity and the reduction of cGMP and epoprostenol content elicited by LDL. However, the elevation of MDA content induced by LDL was negated by TMP only at 150 mg.L-1. TMP also caused a reduction in MDA content and an increase of epoprostenol level in normal endothelial cells. This study suggests that TMP protects endothelial cells against damages elicited by LDL and that the protection of TMP might be due to reduction in lipid peroxidation through stimulation of production and/or release of epoprostenol.